Teaching using the interactive whiteboard and its impact on the achievement of art education students in the subject of sculpture (Journal of the College of Basic Education, 2026)
The current research aims to identify the effect of teaching using the interactive whiteboard on the academic achievement of students of the Department of Art Education in the subject of Sculpture. The research is limited to third-year students in the morning study program and the content of the Sculpture course for the academic year 2025–2026, first semester. It also includes the definition of terms. Chapter Two consists of three sections: teaching, the interactive whiteboard, sculpture, and the indicators of the theoretical framework. Chapter Three presents the research methodology, where the experimental method was adopted. The research population was identified, and a random sample of (70) students was selected. The study defined the objectives, constructed lesson plans and a measurement instrument, which was presented to a group of specialists to establish validity and reliability. The experiment was applied to both the experimental and control groups using several statistical methods. The research concluded that the interactive whiteboard contributed to creating a spirit of teamwork among third-year students in the Sculpture course, as it facilitates the teacher’s ability to monitor students’ responses and evaluate their academic level. The researcher recommended the necessity of equipping classrooms with interactive whiteboards to benefit from them in developing students’ skills and enriching both practical and theoretical subjects. The study also suggested conducting further research on the effect of the interactive whiteboard in developing creative thinking among students of the College of Basic Education in the subjects of Arabic calligraphy and ornamentation. The research concludes with Arabic and foreign references and appendices